Rapid Affinity Purification of Tagged Plant Mitochondria (Mito-AP) for Metabolome and Proteome Analyses. Issue 3 (7th January 2020) - Niehaus, Markus; Straube, Henryk; Künzler, Patrick; Rugen, Nils; Hegermann, Jan; Giavalisco, Patrick; Eubel, Holger; Witte, Claus-Peter; Herde, Marco
Abstract : A focused analysis of the Arabidopsis mitochondrial proteome and key metabolites is facilitated by a rapid tag-based affinity isolation of the whole organelle from small amounts of plant material. Abstract: The isolation of organelles facilitates the focused analysis of subcellular protein and metabolite pools. Here we present a technique for the affinity purification of plant mitochondria (Mito-AP). The stable ectopic expression of a mitochondrial outer membrane protein fused to a GFP:Strep tag in Arabidopsis ( Arabidopsis thaliana ) exclusively decorates mitochondria, enabling their selective affinity purification using magnetic beads coated with Strep-Tactin. With Mito-AP, intact mitochondria from 0.5 g plant material were highly enriched in 30–60 min, considerably faster than with conventional gradient centrifugation. Combining gradient centrifugation and Mito-AP techniques resulted in high purity of >90% mitochondrial proteins in the lysate. Mito-AP supports mitochondrial proteome analysis by shotgun proteomics. The relative abundances of proteins from distinct mitochondrial isolation methods were correlated. A cluster of 619 proteins was consistently enriched by all methods. Among these were several proteins that lack subcellular localization data or that are currently assigned to other compartments. Mito-AP is also compatible with mitochondrial metabolome analysis by triple-quadrupole and orbitrap mass spectrometry. Mito-AP preparations showed a strong enrichment with typical mitochondrial lipids like cardiolipins and demonstrated the presence of several ubiquinones in Arabidopsis mitochondria. Affinity purification of organelles is a powerful tool for reaching higher spatial and temporal resolution for the analysis of metabolomic and proteomic dynamics within subcellular compartments. Mito-AP is small scale, rapid, economic, and potentially applicable to any organelle or to organelle subpopulations.